Alcohol Use in Adolescence and Later Working Memory: Findings From a Large Population-Based Birth Cohort. (10th January 2018) - Mahedy, Liam; Field, Matt; Gage, Suzanne; Hammerton, Gemma; Heron, Jon; Hickman, Matt; Munafò, Marcus R
Abstract: Aims: The study aimed to examine the association between adolescent alcohol use and working memory (WM) using a large population sample. Methods: Data from the Avon Longitudinal Study of Parents and Children were used to investigate the association between alcohol use at age 15 years and WM 3 years later, assessed using the N -back task ( N ~ 3300). A three-category ordinal variable captured mutually exclusive alcohol groupings ranging in order of severity (i.e. low alcohol users, frequent drinkers and frequent/binge drinkers). Differential dropout was accounted for using multiple imputation and inverse probability weighting. Adjustment was made for potential confounders. Results: There was evidence of an association between frequent/binge drinking (compared to the low alcohol group) and poorer performance on the 3-back task after adjusting for sociodemographic confounding variables, WM at age 11 years, and experience of a head injury/unconsciousness before age 11 years ( β = −0.23, 95% CI = −0.37 to −0.09, P = 0.001). However, this association was attenuated ( β = −0.12, 95% CI = −0.27 to 0.03, P = 0.11) when further adjusted for baseline measures of weekly cigarette tobacco and cannabis use. Weaker associations were found for the less demanding 2-back task. We found no evidence to suggest frequent drinking was associated with performance on either task. Conclusions: We found weak evidence of an association between sustained heavy alcohol use in mid-adolescence and impaired WM 3 years later. Although we cannot fully rule out the possibility of reverse causation, several potential confounding variables were included to address the directionality of the relationship between WM and alcohol use problems.